Leere Worte
A short report on Milan Panic's activities as a minister in the former Yugoslavia. Panic organizes a trip to Sarajevo in a push for peace. He designates white armbands as a symbol to be worn by all those who support peace in the region. After landing in Sarajevo with the media in tow, Panic's idealism is quickly grounded by the reality of the situation in Sarajevo. Panic is shown posing for cameras with Gen. Ratko Mladic, commander of the Bosnian Serb army, while promising that the shelling from the surrounding hills will cease on the following day. He then returns to Belgrade to board his own plane for meetings with the UN in New York. In closing, the report cites how fighting resumed as soon as Panic left Sarajevo.